Antithrombotic management in an elderly CABG patient with nephrotic syndrome: a case report - Xu, Feng; Li, Liu-Cheng; Chen, Miao-Miao; Zhao, Long; Zhu, Jian-Ping; Mao, Kai-Li (Frontiers in Cardiovascular Medicine, 2025)
Coronary artery bypass grafting (CABG) is a common treatment for coronary artery disease (CAD), but it poses significant perioperative risks, including thrombosis and bleeding, especially in elderly patients with comorbidities such as nephrotic syndrome and pulmonary infection. Thromboelastography (TEG) has emerged as a valuable tool for guiding dual antiplatelet therapy (DAPT) and optimizing drug treatment strategies in these complex cases. A case presentation of a 65-year-old male patient with nephrotic syndrome and pulmonary infection undergoing CABG surgery was reported. The patient's management included TEG-guided DAPT, routine monitoring of coagulation parameters, and adjustments based on clinical findings and laboratory results. TEG effectively guided DAPT and anticoagulant therapy, ensuring appropriate coagulation status and minimizing bleeding risks. The patient's postoperative management included dual antiplatelet therapy with aspirin and clopidogrel, adjusted based on TEG results. Additional interventions included the use of proton pump inhibitors to prevent gastrointestinal bleeding and tailored antibiotic therapy for pulmonary infection. The patient's clinical outcomes improved, with stable coagulation parameters and controlled infection. Clinical pharmacists play a critical role in optimizing medication regimens and ensuring patient safety through multidisciplinary collaboration. Future studies should further explore the integration of TEG and other advanced tools in personalized pharmaceutical care for complex post-CABG cases.